Degradation of Pesticide Chlorothalonil by Visible Light-Responsive Photocatalyst Ferrioxalate and under Solar Irradiation - Malay Chaudhuri; Hafizi Zuhali; Augustine Chioma Affam (International Journal of Photoenergy)
Ferrioxalate is a visible light-responsive photocatalyst. The solar ferrioxalate/ process has high degradation efficiency because ferrioxalate is able to absorb light strongly at longer wavelength and generates hydroxyl radical with high quantum yield. Degradation of pesticide chlorothalonil in aqueous solution by ferrioxalate/ under solar irradiation was examined. The optimum operating conditions for treatment of a 300 mg/L chlorothalonil aqueous solution were obtained by using the central composite design of the response surface methodology. Under the optimum operating conditions (/COD molar ratio 2.75, /Fe3+ molar ratio 75, /C2H2O4 molar ratio 37.5, reaction time 90 min, and pH 3), COD, NH3-N, and TOC removal of 75.71, 47.11, and 54.33%, respectively, was achieved and the biodegradability (BOD5/COD ratio) improved from zero to 0.42. Model prediction and actual removal were in close agreement (<4% error). The solar ferrioxalate/H2O2 process is effective in pretreatment of the chlorothalonil aqueous solution for biological treatment.